1982
DOI: 10.1080/03014468200006041
|View full text |Cite
|
Sign up to set email alerts
|

The blood groups and other hereditary blood factors of the Icelanders

Abstract: Bjarnason, Bjarnason, Edwards, Fridriksson, Magnusson, Mourant and Tills (1973) published preliminary data on a study of Iceland. The present paper gives the complete data of the study and extends the sample size for most of the genetic systems to over 1500 individuals, approximately 1/130 of the population. The sample was divided into seven subpopulations and these were compared using a genetic distance matrix. Considerable internal variation was revealed with two groups appearing very different. The seven re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Why has P. falciparum evolved so many pathways for invasion? The erythrocyte surface molecules are highly polymorphic within the human population (34)(35)(36)(37)(38). It has been reported that the fastest evolving genes in the human lineage are the glycophorins A and B (39).…”
Section: Discussionmentioning
confidence: 99%
“…Why has P. falciparum evolved so many pathways for invasion? The erythrocyte surface molecules are highly polymorphic within the human population (34)(35)(36)(37)(38). It has been reported that the fastest evolving genes in the human lineage are the glycophorins A and B (39).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the PGM1 allele in the Icelandic population (in the present study) is lower than that observed by Bjarnason at a1. (1973) and Tills et al (1982); consequently, the frequency of PGM1 2 is higher. The Icelandic population with PGM1 1 and PGM1 2 gene frequencies of 0,7999 and 0,2001, respectively, as found from isoelectric focusing, shows a greater similarity to the reported Danish, Swedish and Norwegian gene frequencies, than to those reported for the Irish population.…”
Section: Resultsmentioning
confidence: 94%
“…They are, respectively, 0,7999 for PGM1 and 0,2001 for PGM1 2, and can therefore be compared with the results of the study by Bjarnason et a1. (1973) and Tills et al (1982) on the distribution of PGM1 by using a system of three "old" phenotypes: PGM1 1, PGM1 2 and PGM1 2-1 (Table 4). The frequency of the PGM1 allele in the Icelandic population (in the present study) is lower than that observed by Bjarnason at a1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if the antigen is absent in a population, that tribe may have arrived prior t o carriers of the gene. Tills (1982) suggests that there may have been as many as five migra-tions of Indians in the Americas with varying percentages of Dia genes in these populations. The recent review by Szathmary (1984) examines the question of a single migration or multiple migrations from Asia to America and is of particular interest.…”
Section: Discussionmentioning
confidence: 99%